Decentralised Finance (Defi) and Financial Inclusion in Uganda: An Appraisal of the Legal Framework and Its Adequacy for the Regulation of Decentralised Finance - Eugene Kironde (Uganda Christian University, 2025)
This study examines the potential of Decentralised Finance (DeFi) to enhance financial inclusion in Uganda and it appraises the adequacy of the current legal and regulatory frameworks in governing DeFi systems. DeFi operates in a vacuum in Uganda, with the Bank of Uganda and the key stakeholders having expressed conservative approaches its regulation. Using a doctrinal and comparative research methodology, this dissertation evaluates whether Uganda’s key financial laws are compatible with emerging DeFi technologies. It explores the non-legal dimensions such as digital literacy, infrastructural barriers and socio economic divides that influence actively DeFi adoption in Uganda. The study draws on international best practises highlight how countries have responded to the unique challenges posed by Decentralised Finance, key among these which include governance risks, regulatory uncertainty and smart contract vulnerabilities. The findings reveal that while DeFi holds a key potential in increasing financial access particularly among the unbanked populations, its unregulated state introduces significant risks to consumer protection, accountability and financial stability. Uganda’s existing legal regime is ill equipped to address the technical and operations complexities of DeFi, particularly its decentralised governance models like DAOs and smart contracts. The study concluded by recommending the development of a tailored legal and regulatory framework that balances innovation with oversight. Key proposals include the establishment of a regulatory sandbox, institutional capacity building and the legal recognition of DeFI service providers under a reformed digital financial services regime. By addressing both the opportunities and risks of DeFi, this research contributes to ongoing discussions on how Uganda can safely integrate decentralised finance to promote inclusive finance.
Keywords: Decentralised finance (DeFi); Financial inclusion; Legal framework; Block chain; Regulation; Smart contracts; DAOs